2020
DOI: 10.1101/2020.10.03.324947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual coupling and decoupling of the default mode network during mind-wandering and reading

Abstract: Semantic cognition can be both perceptually-coupled, for example, during reading, and decoupled, such as in daydreams. Mind-wandering, characterised by autobiographical memory retrieval, often interferes with externally-focussed tasks. This study investigated the neural basis of these states, when they occur in isolation and in competition, using fMRI. Participants were asked to read sentences, presented word-by-word, or to recall personal memories, as a proxy for mind-wandering. Task conflict was created by p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 113 publications
(186 reference statements)
0
5
0
Order By: Relevance
“…Just as we found a control network that was closer to the heteromodal end of the principal gradient in the left hemisphere, DMN-B (the adjacent network), showed the same pattern. DMN-B includes regions such as lateral ATL, angular gyrus, inferior frontal gyrus and dorsomedial prefrontal cortex that are associated with semantic processing in the left hemisphere (Jackson 2021;Jefferies 2013;Lambon Ralph et al 2017;Noonan et al 2013;Rice et al 2015b), and this DMN variant has repeatedly shown functional dissociations with core DMN regions such as posterior cingulate cortex and more ventromedial prefrontal regions (Chiou et al 2020;Zhang et al 2020), referred to here as DMN-A. DMN-B is associated with lateralised cognitive processes, like language and semantics, as well as social cognition (Andrews-Hanna et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Just as we found a control network that was closer to the heteromodal end of the principal gradient in the left hemisphere, DMN-B (the adjacent network), showed the same pattern. DMN-B includes regions such as lateral ATL, angular gyrus, inferior frontal gyrus and dorsomedial prefrontal cortex that are associated with semantic processing in the left hemisphere (Jackson 2021;Jefferies 2013;Lambon Ralph et al 2017;Noonan et al 2013;Rice et al 2015b), and this DMN variant has repeatedly shown functional dissociations with core DMN regions such as posterior cingulate cortex and more ventromedial prefrontal regions (Chiou et al 2020;Zhang et al 2020), referred to here as DMN-A. DMN-B is associated with lateralised cognitive processes, like language and semantics, as well as social cognition (Andrews-Hanna et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…– for example, when linking dog to beach, activation might be focussed on running, swimming and digging actions, as opposed to the physical features of a dog (such as its ears and tail). These features are thought to rely on interactions between the heteromodal ‘hub’ within anterolateral temporal cortex and ‘spoke’ systems in unimodal cortex; consequently, semantic control processes could bias activation towards relevant spoke systems, resulting in a more relevant response within the heteromodal hub when these features are distilled into a coherent meaning (Jackson et al 2019; Zhang et al 2020). This process could be largely analogous to the way that MDN regions are thought to bias processing towards task-relevant inputs or sensory features.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the dorsomedial DMN subsystem, which encompasses anterior ventral parts of inferior frontal gyrus as well as temporal and parietal regions, responded during the retrieval of weaker and unique associations that were more reliant on semantic memory alone, with no activation in the core DMN. Large-scale meta-analyses have implicated dorsomedial DMN in conceptual processing (Andrews-Hanna et al, 2010; Andrews-Hanna et al, 2014), while the core and medial DMN subsystems show greater recruitment during episodic memory (Huijbers et al, 2011; Sestieri et al, 2011), past and future autobiographical thought and self-referential processing (Andrews-Hanna et al, 2010; Andrews-Hanna et al, 2014; Chiou et al, 2020; Zhang et al, 2021). In addition, the dorsomedial DMN but not the core DMN (as defined by a parcellation of resting-state fMRI of 1000 brains) overlaps with the functionally-defined SCN; this provides further evidence that dorsomedial DMN supports both automatic and controlled aspects of semantic cognition.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a ‘core’ DMN subsystem shows greater task-related deactivation, particularly during challenging decisions, and no overlap with SCN (Figure 1). These DMN subsystems have been differentially implicated in semantic (dorsomedial DMN) and episodic (core) processes (Zhang et al, 2021).…”
Section: Figurementioning
confidence: 99%